Disassembly of the lens fiber cell nucleus to create a clear lens: The p27 descent. (March 2017) - Rowan, Sheldon; Chang, Min-Lee; Reznikov, Natalie; Taylor, Allen
Abstract: The eye lens is unique among tissues: it is transparent, does not form tumors, and the majority of its cells degrade their organelles, including their cell nuclei. A mystery for over a century, there has been considerable recent progress in elucidating mechanisms of lens fiber cell denucleation (LFCD). In contrast to the disassembly and reassembly of the cell nucleus during mitosis, LFCD is a unidirectional process that culminates in destruction of the fiber cell nucleus. Whereas p27 Kip1, the cyclin-dependent kinase inhibitor, is upregulated during formation of LFC in the outermost cortex, in the inner cortex, in the nascent organelle free zone, p27 Kip1 is degraded, markedly activating cyclin-dependent kinase 1 (Cdk1). This process results in phosphorylation of nuclear Lamins, dissociation of the nuclear membrane, and entry of lysosomes that liberate DNaseIIβ (DLAD) to cleave chromatin. Multiple cellular pathways, including the ubiquitin proteasome system and the unfolded protein response, converge on post-translational regulation of p27 Kip1 . Mutations that impair these pathways are associated with congenital cataracts and loss of LFCD. These findings highlight new regulatory nodes in the lens and suggest that we are close to understanding this fascinating terminal differentiation process. Such knowledge may offer a new means to confront proliferative diseases including cancer. Highlights: Lens fiber cells must remove their nuclei to establish a clear lens. Fiber cells borrow mitotic machinery to disassemble their nuclear envelope. Cdk1 is essential for denucleation and is inhibited by p27. Ubiquitin pathway and unfolded protein response converge to regulate p27 levels. Lysosomes fuse with or enter the nucleus and deliver DNaseIIβ to degrade chromatin.